Analysis of Root Canal Anatomy of Mandibular Permanent Incisors in Saudi Subpopulation: A Cone-Beam Computed Tomography (CBCT) Study. (19th May 2022) - Almohaimede, Amal; Alqahtani, Alanoud; Alhatlani, Norah; Alsaloom, Nouf; Alqahtani, Shafia
Abstract : This study aimed to evaluate the root canal anatomy of central and lateral mandibular incisors in a Saudi population using cone-beam computed tomography (CBCT). Overall, 1370 CBCT images of central (687) and lateral (683) mandibular incisors of Saudi patients who attended the Dental College at King Saud University in Riyadh were examined. The number of roots and canals, canal configuration types, symmetry between bilateral incisors, and the effect of gender and age were determined. For data analysis, the chi-square test was applied, and the p value was set at ≤0.05. Only one tooth had two roots, and 41% of mandibular incisors had two canals. The most common canal configuration type observed was type I (58.83%), followed by type III (28.24%). Type V was more common in men (8.31%) than women (3.9%). Bilateral symmetries were higher in the mandibular central incisors regarding the root and canal numbers and the canal configuration types (100, 100, and 97.92%, respectively) than in the lateral incisors (99.69, 98.16, and 97.24%, respectively). The 21–40 age group showed a higher proportion of teeth with more complicated root canal anatomy than the other age groups. More than one canal in mandibular incisors is a common finding in the Saudi subpopulation, with the type III canal configuration as the most common type.